Penilaian Erosi Tanah dan Sedimen pada Ekosistem Rawa Pegunungan menggunakan Model InVEST-SDR (Studi Kasus DAS Cidanau): Soil Erosion and Sediment Assessment at Mountainous Swamp Ecosystem using InVEST-SDR Model (Case Study Cidanau Watershed) - Sri Malahayati Yusuf; Tri Handayani; Gilang Munggaran; Kartika Triasary; Bagus Budiprakoso (Universitas Hasanuddin, 2026)
The Cidanau watershed is a unique hydrological region in Indonesia, distinguished by its mountainous swamp ecosystem. As a vital source of raw water for the surrounding communities, maintaining ecological sustainability is essential. This study aimed to evaluate soil erosion and sedimentation in the Cidanau watershed, focusing on the existing conditions and activity of forest and land rehabilitation. The rehabilitation program consists of vegetative and mechanical methods of soil and water conservation. The analysis was conducted using the InVEST-SDR model, integrated with a geographic information system, incorporating data on rainfall, soil characteristics, topography, land use, and conservation practices. Soil samples were collected using a stratified method from nine land units. The land use map for 2022 was improved using high-resolution imagery data and drone mapping. The results indicate that implementing vegetative and mechanical methods of soil and water conservation can decrease soil erosion and sedimentation. In detail, the area classified under very low erosion increased by 41%, while the areas with low, medium, high, and very high erosion decreased by 14.3, 24.6, 42.7, and 42.5%, respectively, compared to the existing scenario. Additionally, sediment levels declined, with the area under very low sedimentation increasing by 31.5% compared to the existing levels. These findings demonstrate that the implementation of soil and water conservation techniques effectively enhances watershed health and supports the long-term sustainability of water resources.